World Bank Operations Evaluation Department : the first 30 years - Grasso, Patrick; Wasty, Sulaiman S.; Weaving, Rachel, 1947- (World Bank, 2003)
During the course of 2002-03 the Bank's Operations Evaluation Department (OED) held a series of major events, including seminars and workshops, leading up to the thirtieth anniversary of the founding of OED by Robert McNamara on July 1, 1973. This volume captures the history of OED as related by many of those who participated in making that history. It is divided into four sections. The first part is drawn from a series of presentations made by former directors-general, Operations Evaluation, and senior OED managers. It relates, in roughly chronological presentations, the development of OED from an experimental program to a major department with a record of accomplishment and influence within the Bank and beyond. The second part presents perspectives on OED from two of its most important internal constituencies-the Board of Executive Directors and senior Bank management. Part three considers OED's relationships with its external constituents, including its work on developing evaluation capacity among client countries and its evaluation partnerships with other development organizations. Finally, part four presents a forward-looking appraisal of the challenges of development evaluation from three of its leading